2013
DOI: 10.1186/1752-153x-7-41
|View full text |Cite
|
Sign up to set email alerts
|

TiO2-graphene oxide nanocomposite as advanced photocatalytic materials

Abstract: BackgroundGraphene oxide composites with photocatalysts may exhibit better properties than pure photocatalysts via improvement of their textural and electronic properties.ResultsTiO2-Graphene Oxide (TiO2 - GO) nanocomposite was prepared by thermal hydrolysis of suspension with graphene oxide (GO) nanosheets and titania peroxo-complex. The characterization of graphene oxide nanosheets was provided by using an atomic force microscope and Raman spectroscopy. The prepared nanocomposites samples were characterized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
96
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 232 publications
(102 citation statements)
references
References 33 publications
5
96
0
1
Order By: Relevance
“…In the nanocomposite sample, copper oxide nanoparticles are coated with SiO 2 nanoparticles. Therefore, when the surface area of CuO/SiO 2 nanocomposites is measured, it is possible that its size is dominantly determined by the surface properties of the amorphous SiO 2 rather than CuO [34]. For this reason, a relatively low specific surface of the CuO/SiO 2 nanocomposites is apparent compared to that of CuO nanoparticles.…”
Section: Bet Analysismentioning
confidence: 99%
“…In the nanocomposite sample, copper oxide nanoparticles are coated with SiO 2 nanoparticles. Therefore, when the surface area of CuO/SiO 2 nanocomposites is measured, it is possible that its size is dominantly determined by the surface properties of the amorphous SiO 2 rather than CuO [34]. For this reason, a relatively low specific surface of the CuO/SiO 2 nanocomposites is apparent compared to that of CuO nanoparticles.…”
Section: Bet Analysismentioning
confidence: 99%
“…The relative sensitivity factors of carbon and oxygen were obtained from CASA XPS standard table. 40 The calculated C/O ratio of GO and RGO samples are summarised in Table 2. Tables 3 and 4 show the tted results of carbon (C 1s) and oxygen (O 1s) XPS spectra of RGO samples, respectively.…”
mentioning
confidence: 99%
“…For its particular properties and for its higher amount of accessible surface area, porous graphene could be a promising candidate as material for the development of new TiO 2 -porous graphene nanocomposites. A first study has been conducted by Stengl [111], where they synthesized mesoporous TiO 2 -graphene oxide nanocomposites with a specific surface area of almost ∼80-200 m 2 g −1 , larger than those of TiO 2 nanoparticles (P25) [108].The authors reported a better photocatalytic degradation of butane in the gas phase attributed different effects including the increase in specific surface area. By developing suitable nano-manipulation and nano-assembling techniques [112] porous graphene is a very attractive materials for a range of applications.…”
Section: Discussionmentioning
confidence: 99%